2022
DOI: 10.1016/j.jrurstud.2022.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Diverse adaptation strategies helped local food producers cope with initial challenges of the Covid-19 pandemic: Lessons from Québec, Canada

Abstract: The Covid-19 pandemic has demonstrated the vulnerability of food systems to disturbances. Advocates have promoted short food supply chains as more resilient and adaptable thanks to their embeddedness in local economic and ecological networks. As part of a broader case study on challenges facing farmers in local food supply chains in Québec, Canada, we asked farmers about the pandemic's impacts on food production and marketing in the province, including how food producers coped with these challenges. We sent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…In concert with our previous study on the same farmer population, which indicated that farmers perceived environmental challenges as more severe than those arising from the Covid-19 pandemic-related impacts (Schreiber et al 2022 ), we suggest that farmers would benefit from more systemic and formal support at various levels, especially moderated and facilitated by associations. Associations played a particularly important role for the local farming community as they served many needs and helped to access different types of resources to address farmers’ challenges.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In concert with our previous study on the same farmer population, which indicated that farmers perceived environmental challenges as more severe than those arising from the Covid-19 pandemic-related impacts (Schreiber et al 2022 ), we suggest that farmers would benefit from more systemic and formal support at various levels, especially moderated and facilitated by associations. Associations played a particularly important role for the local farming community as they served many needs and helped to access different types of resources to address farmers’ challenges.…”
Section: Discussionsupporting
confidence: 83%
“…A total of 8% of our survey respondents sent food to the US and 2% internationally. Most survey respondents used farm stores (62%) to sell their food, followed by independent grocery stores (44%), restaurants (42%), and public and farmers markets (41%) (Schreiber et al 2022 ). Overall, close to 60% sold their products directly to consumers and through intermediaries, whereas a quarter of respondents sold only to end consumers, and 9% only to intermediaries (SI Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations